The Role of Autophagy in the Function of CD4+ T Cells and the Development of Chronic Inflammatory Diseases - Jeong, Jiung; Choi, Young Joon; Lee, Heung Kyu (Frontiers in Pharmacology, 2022)
Uncontrolled acute inflammation progresses to persistent inflammation that leads to various chronic inflammatory diseases, including asthma, Crohn’s disease, and rheumatoid arthritis. CD4+ T cells are key immune cells that determine the development of these chronic inflammatory diseases. CD4+ T cells orchestrate adaptive immune responses by producing cytokines and effector molecules. These functional roles of T cells vary depending on the surrounding inflammatory or anatomical environment. Autophagy is an important process that can regulate the function of CD4+ T cells. By lysosomal degradation of cytoplasmic materials, autophagy mediates CD4+ T cell-mediated immune responses, including cytokine production, proliferation, and differentiation. Furthermore, through canonical processes involving autophagy machinery, autophagy also contributes to the development of chronic inflammatory diseases. Therefore, a targeted intervention of autophagy processes could be used to treat chronic inflammatory diseases. This review focuses on the role of autophagy via CD4+ T cells in the pathogenesis and treatment of such diseases. In particular, we explore the underlying mechanisms of autophagy in the regulation of CD4+ T cell metabolism, survival, development, proliferation, differentiation, and aging. Furthermore, we suggest that autophagy-mediated modulation of CD4+ T cells is a promising therapeutic target for treating chronic inflammatory diseases.